Early Childhood’s Dynamics of Socio-Emotional Development: COVID-19 Pandemic vs Post COVID-19 Pandemic - Nadlifah, Nadlifah; Rahmatu Kirana, Ejia; Puspawati, Dera (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – The limited interaction among children in early childhood learning during the COVID-19 pandemic causes the lack of fulfilment of children’s socio-emotional development. This study aims at analyzing the dynamics of socio-emotional development occurred in TK Nurul Islam during the COVID-19 pandemic.Design/methods/approach – The research design of this study is qualitative research. The data are collected through observation, interviews, and documentation. Then, the data are analyzed using Milles and Huberman models. To test the validity of the data, source triangulation and technical triangulation are used.Findings – The findings of this study explain that the socio-emotional development of children in TK Nurul Islam during the pandemic has not developed well. Some habitual actions encouraged by teachers —such as smiling, greetings, memorizing some short surahs, mentoring students, and having fun learning are able to stimulate children’s socio-emotional development after the COVID-19 pandemic. As a result, children’s socio-emotional development after the COVID-19 pandemic can develop well as expected.Research implications/limitations – This study is only limited on the aspects of early childhood’s socio-emotional development.Practical implications – This study contributes to the knowledge and provides the examples of teachers’ practice in developing children’s socio-emotional development in early childhood education institutions.Originality/value – Research can be used as an evaluation to develop children’s socio-emotional development during the pandemic and after the COVID-19 pandemic.Paper type: Research paper